5G‐based remote magnetically controlled capsule endoscopy for examination of the stomach and small bowel. Issue 1 (23rd November 2022) - Zhang, Ting; Chen, Yi‐Zhi; Jiang, Xi; He, Chen; Pan, Jun; Zhou, Wei; Hu, Jian‐Ping; Liao, Zhuan; Li, Zhao‐Shen
Abstract: Background and aims: Remote endoscopy can improve diagnostic efficiency of gastrointestinal (GI) diseases for patients in remote areas. A novel remote magnetically controlled capsule endoscopy (MCE) system based on a 5G network was developed for real‐time remote GI examinations. We aimed to evaluate the feasibility and safety of the 5G‐based remote MCE for examination of the stomach and small bowel. Methods: This was a prospective, nonrandomized, comparative study. Consecutive participants enrolled in the First People's Hospital of Yinchuan underwent remote MCE examinations performed by an endoscopist located in Changhai Hospital. Consecutive participants enrolled in Changhai Hospital underwent conventional MCE examinations performed by the same endoscopist. The main outcomes included the complete visualization rate of the stomach and small bowel, safety assessment and network latency time of remote MCE examinations. Results: From March 2021 to June 2021, 20 participants in each group were enrolled. The complete visualization rate of the stomach and small bowel was 100% in both groups ( p > 0.999) without any adverse event. The median network latency time of remote MCE group was 19.948 ms. Gastric examination time (8.96 vs. 8.92 min, p = 0.234), maneuverability (15.00 vs. 15.00, p = 0.317), image quality (1.00 vs. 1.00, p > 0.999) and diagnostic yields in the stomach and small bowel (55% vs. 30%, 5% vs. 0%, both p > 0.05) were comparable between remote and conventional MCE groups. All participants in remote MCE group considered remote MCE acceptable and necessary. Conclusions: 5G‐based remote MCE was a feasible and safe method for viewing the stomach and small bowel.